Role of Hydrology in Managing Consequences of a Changing Global Environment 2010
DOI: 10.7558/bhs.2010.ic39
|View full text |Cite
|
Sign up to set email alerts
|

Runoff management: mitigation measures for disconnecting flow pathways in the Belford Burn catchment to reduce flood risk.

Abstract: Evidence that intensive farming leads to increased runoff rates has been established. Fast, well connected flow paths are clearly contributing to the 'muddy floods' observed at the local scale. By targeting runoff in fields and farm ditches then a significant component of flood generation can potentially be managed at the catchment scale. The Belford Burn (Northumberland, UK) catchment is a small rural catchment with a catchment area of 6 km 2. Normal flood defences are not suitable for this catchment as it fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…In some cases, like the floods in December 2015 in the North West of England, “hard” flood mitigation measures were overwhelmed, where design standards are exceeded. The “soft” measures include changes in vegetation cover (including forestation), land management, improvements of water channels, improvements of drainage system, and diversions of water ways or rivers (for a full discussion see Wilkinson, Quinn, Benson, & Welton, ). Taking passive approaches involves doing little to control flood events and instead diverting investment to compensate victims, improving community awareness of flood risk, and subsidising insurance policies.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, like the floods in December 2015 in the North West of England, “hard” flood mitigation measures were overwhelmed, where design standards are exceeded. The “soft” measures include changes in vegetation cover (including forestation), land management, improvements of water channels, improvements of drainage system, and diversions of water ways or rivers (for a full discussion see Wilkinson, Quinn, Benson, & Welton, ). Taking passive approaches involves doing little to control flood events and instead diverting investment to compensate victims, improving community awareness of flood risk, and subsidising insurance policies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus we could not confirm the positive effect of the use of drainage ditches on soil water storage capacity as mentioned by, for example, Horton (), Thomasson (), and Wilkinson et al . (). The best model explaining kurtosis of the runoff hydrographs was a multiple regression equation where SBD and FD explain 83% of its variability (Equation ).…”
Section: Discussionmentioning
confidence: 97%
“…Capturing data during storm events is critical for presenting the evidence of RAFs to stakeholders and extremely useful for suggesting improvements to their functioning. Wilkinson et al . (2010a) analysed data for the pilot pond functioning during a double‐peaked storm event in September 2008, which indicated that the drainage rate was insufficent.…”
Section: Runoff Attenuation Features (Rafs) In the Belford Burn Catchmentioning
confidence: 99%
“…The construction of LWD came with an opportunistic decision to have sycamore trees removed and replaced with less intrusive suitable tree species. The LWD and associated floodplain barriers were located at six locations (15 m apart) over the reach of the stream within a wooded riparian zone (Wilkinson et al . 2010a).…”
Section: Runoff Attenuation Features (Rafs) In the Belford Burn Catchmentioning
confidence: 99%